Development of a VOC (Volatile Organic Compound) Measurement System to Identify Placebo Phenomenon in Emission Areas - Alhadawiah, Sabila; Wirawan, Rahadi; Budianto, Arif (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2024)
VOCs (volatile organic compounds) can be used as a biomarker of placebo phenomenon, such as stress, panic disorder, health conditions, and many others. VOCs from the exhaled breath have different concentration levels that are also related to many health diseases. However, the use of VOCs as biomarkers in exhaled breath are very limited. Hence, this study aims to develop a novel e-nose (electric nose) system based on a VOC measurement system to identify placebo phenomenon in emission areas. For this purpose, a digital semiconductor VOC sensor and a microcontroller were used to detect VOC level. The developed system was tested inside a chamber for the initial calibration and comparation steps using fresh air and a comparator device. After calibration, the system was used to measure the VOC concentrations of 20 exhaled breath samples in the emission sampling areas (control and emission sources). In other sides, the VOC levels surrounding the emission areas were also measured using the comparator device. The placebo levels (PLS) of the exhaled breath samples were divided into PLS(-) or placebo negative and PLS(+) or placebo positive related to the placebo conditions. The sampling areas were divided into indoor and outdoor areas to identify the different placebo percentages and the dependence related to the emission levels. The results show that the emission levels of the emission sources are about 504-528 ppb, meanwhile, the control area (clean area) has <10 ppb of VOC levels. A higher VOC concentration, a higher PLS(+) percentage. The exhaled breath of PLS(+) samples contain >78 ppb of VOC levels, while PLS(-) samples has < 78 ppb of VOC levels (p < 0.05). It can be concluded that VOC concentrations in the emission sources has a potential to influence the placebo quantification in human psycological health. The developed e-nose system can be used to identify VOC levels as a biomarker of a placebo phenomenon.